2021
DOI: 10.51253/pafmj.v71i1.3693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella Sativa on Serum Testosterone Levels in Letrozole Induced Polycystic Ovarian Syndrome in Mice

Abstract: Objective: Monitor the ameliorative impact of Nigella sativa on fasting blood glucose and serum testosteronelevels in polycystic ovarian syndrome caused by letrozole in mice. Study Design: Laboratory based randomized control trial. Place and Duration of Study: Anatomy department, Army Medical College in teamwork with National Instituteof Health. Time span is Dec 2014 Dec 2015. Methodology: Total 40 mature female BALB/c mice were chosen and distributed in four groups (ten mice in each one). Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The ovarian weight of animals of group-2 was increased as compared to group-1 and it was statistically significant. This increased ovarian weight was due to increased stromal tissuse and increase in number of follicles including cystic follicles 19 . Ovarian weight of animals of group-3 and 4 was reduced as compared to group-2 and it was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian weight of animals of group-2 was increased as compared to group-1 and it was statistically significant. This increased ovarian weight was due to increased stromal tissuse and increase in number of follicles including cystic follicles 19 . Ovarian weight of animals of group-3 and 4 was reduced as compared to group-2 and it was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Noreen Anwar, et al conducted an experiment to investigate Nigella sativa at doses of 1 and 4 mg/Kg BW in PCOS mice showed that there was a decrease in the number of cystic follicles [11].…”
Section: Study In Humanmentioning
confidence: 99%
“…Polycystic ovary (Stein Leventhal Syndrome) is one of the major endocrine and metabolic disorders of women affecting approximately 4-10% women of reproductive women [1,2]. It is characterized by hyperandrogenism, multiple small ovarian cysts, irregular menstrual cycles, and anovulation.…”
Section: Introductionmentioning
confidence: 99%